Economic Analyses in Watershed Management Planning: Methods, Applications and Education - de Steiguer, J E; Crimmins, Theresa Man (Annals of Arid Zone, 2016)
The management of watersheds is most commonly thought to involve the hydrological, physical, biological and engineering sciences. However, economics also has a role in watershed management planning. Cost-benefit analysis (CBA) is the most common type of economic analysis used for watershed planning. CBA measures, in monetary terms. a project’s inputs and outputs over the service life of the project. Under CBA, a project that yields discounted net benefits which exceed costs, is said to be "economically efficient." Economically efficient projects are desirable because they represent a potential Pareto improvement, which is to say that society can gain an economic surplus, hence a net improvement, from the activity. CBA is a useful decision method when the watershed manager must make a decision based solely upon economic efficiency. However, watershed managers frequently must deal with multiple decision criteria. Multi-Criteria Decision Models (MCDMs) have been developed for such situations. "Economics" can enter into MCDMs as one of the decision criteria. Examples of MCDMs include linear and goal programming, Multi-Attribute Utility Theory and the Analytic Hierarchy Process. With regard to the study of economics in watershed management curricula in American universities, economics and the management sciences play a small but important role in watershed education. However, with the trend toward greater stakeholder participation in watershed decisions, future curricula could see a greater demand for more social and management science courses.